Employee pro-environmental proactive behavior: the influence of pro-environmental senior leader and organizational support, supervisor and co-worker support, and employee pro-environmental engagement - Albrecht, Simon L.; Dalton, Jack R.; Kavadas, Vicki (Frontiers in Sustainability, 2024)
Organizations are increasingly being held to account by a broad range of stakeholders to deliver products and services in an environmentally sustainable way. Within this context, employees are increasingly being recognized as important to the successful implementation of organizational environmental policies, procedures, practices, and initiatives. For organizations to successfully achieve environmental objectives, they need to enable a range of supports that promote employee enthusiasm for pro-environmental action, and that motivate employees to proactively engage in pro-environmental behaviors. The present study contributes to the employee sustainability literature by showing how four different sources of pro-environmental support influence employee pro-environmental engagement and pro-environmental proactive behavior. More specifically, and drawing from organizational support and engagement theory, the study tests a model analysing the impact of pro-environmental senior leader support, pro-environmental organizational support, pro-environmental supervisor support, and pro-environmental co-worker support on pro-environmental engagement, and, in turn, on pro-environmental proactive behavior. On-line survey responses from 347 Australian employees aged from 18 to 80 years old, working full-time or part-time, in a variety of industries were analyzed. Confirmatory factor analyses and structural equation modelling revealed support for the validity of the measures and for the relationships proposed. Overall, taking account of direct and indirect effects, the model accounted for 64% of the variance in pro-environmental engagement, and 43% of the variance in pro-environmental proactive behavior. All four sources of support significantly predicted pro-environmental engagement and, as proposed supervisor, coworker support, and pro-environmental engagement predicted pro-environmental proactive behavior. Relative weights analysis established that pro-environmental coworker support was the strongest predictor of pro-environmental engagement and proactive behavior. The results extend pro-environmental engagement theory by showing how different sources of pro-environmental support influence employee pro-environmental motivation and proactive behavior. The research also extends previous theory and research by showing that pro-environmental engagement had a significant influence on employee proactive behavior. Overall, the research suggests that through a focus on the provision of a range of supports, organizations can implement targeted and evidence-based employee-centred initiatives to become more sustainable, and to better meet their pro-environmental strategic goals.